INTEGRASI BUDAYA LOKAL ANYAMAN DESA SUNGAI LIUK DALAM PEMBELAJARAN MATEMATIKA PADA MATERI GEOMETRI MENGGUNAKAN GEOGEBRA - Yelza Elin Ndani; Rahmi Putri; Mesi Oktafia (JP2M (Jurnal Pendidikan dan Pembelajaran Matematika), 2025)
The purpose of this research is to explore and introduce local culture in the form of woven crafts that contain the concept of geometry of curved surface solids, aided by GeoGebra media that can model the mathematical concepts embedded in the weaving culture. This research is descriptive in nature. From the student assessment sheets, it is evident that students have started to understand the concept of mathematics, especially in the topic of curved surface solids. In their learning, this is linked with the use of GeoGebra as a learning medium, which can serve as an effective learning resource for students in realizing cultural objects into the media used. This can enhance students' imagination in studying these solids, making it easier for them to remember and learn the material being discussed. Although there are students who do not yet understand the concept of curved surface solids in mathematics, the use of media as a learning support, especially GeoGebra, will be very helpful if a teacher uses it in accordance with the material being discussed and the needs of the students. Engaging media will attract students to learn because in this advanced era, many students are reluctant to study due to boring teaching methods. Therefore, it’s important for a teacher to create engaging learning media to attract students to learn.